Gelling properties of black soldier fly (Hermetia illucens) larvae protein after ultrasound treatment. (30th August 2022) - Kumar, Sruthi; Queiroz, Lucas Sales; Marie, Rodolphe; Nascimento, Luis Gustavo Lima; Mohammadifar, Mohammad Amin; de Carvalho, Antonio Fernandes; Brouzes, Chloé Marie Charlotte; Fallquist, Heather; Fraihi, Wael; Casanova, Federico
Graphical abstract: Highlights: Significant impact of ultrasound treatment on size and surface hydrophobicity of BSFL protein. Improvement of water holding capacity and gelling properties of treated samples. High elastic modulus after 15 min of ultrasound treatment. CLSM images coupled with 2-D correlation analysis confirmed the different gel structures. Abstract: H. illucens, black soldier fly larvae (BSFL) is one of the sustainable sources of protein. However, the research on the functionality of BSFL proteins is limited and need to be explored to increase consumer acceptance. The aim of this study is to create a gel system from BSFL protein and evaluate the impact of ultrasound treatment at different exposure time (5, 15, 30 min) on the physicochemical properties of BSFL protein. The highest values for surface hydrophobicity, size, ζ-potential were obtained after 15 min of ultrasound treatment and the same was found for the elastic modulus. Finally, confocal laser scanning microscopy (CLSM) along with image analysis revealed the lowest pore size after 15 min of treatment. The high protein content of BSFL protein extract and its promising gel system herein created, are important features to be considered for further development of insect-based food.